Diagnosis acceptance, masking, and perceived benefits and challenges in adults with ADHD and ASD: associations with quality of life - Wurth, Paula; Fuermaier, Anselm BM; Strand, Anne Hege; Thorell, Lisa B. (Frontiers in Psychiatry, 2025)
ObjectivesResearch has increasingly focused on neurodivergent individuals’ acceptance of their diagnosis and the extent to which they engage in masking behaviors. However, there is a lack of large-scale quantitative investigations. This study, therefore, examined how young adults with attention deficit hyperactivity disorder (ADHD) and/or autism spectrum disorders (ASD) perceive and relate to their diagnosis in terms of diagnosis agreement, diagnosis liking, masking, perceived benefits/challenges, and how these constructs are related to one another and to quality of life.MethodsThe sample included adults with ADHD (n = 803), ASD (n = 158), or both ADHD and ASD (n = 95). Participants (aged 18-35; 79% females) completed an online survey assessing diagnosis acceptance, perceived benefits and challenges, masking, and quality of life.ResultsThe participants reported high agreement with their diagnosis (95%), but fewer liked their diagnosis (29%), and masking behavior varied by context. Participants reported experiencing both benefits (e.g., “seeing things my own way” and “drive to find things out”) and challenges (e.g., “mentally exhausting” and “being misunderstood”) related to their diagnosis. Quality of life was associated with all other variables, but most strongly associated with perceived benefits.ConclusionsThis study shows that adults with ADHD and/or ASD generally agree with their diagnosis, but the extent to which they like their diagnosis varies. Masking is commonly reported and depends on the context. Perceiving benefits was the variable most strongly associated with quality of life, highlighting the importance of clinical approaches promoting strength-based perspectives rather than a strict deficit approach.